HAMBATAN PELAKSANAAN PERMOHONAN EKSTRADISI DALAM HUKUM PIDANA DI INDONESIA (STUDI PUTUSAN NOMOR: 369/PID.SUS/2020/PT.DKI.JKT jo.NOMOR 104/PID.C.EKSTRADISI/2020/PN.JKT.SEL.) - I Gde Eka Haryana, (2022)
This research was conducted using normative legal research methods, as well as an empirical legal approach by taking into account the facts that occurred in the field related to the implementation of the examination of extradition requests. The study was conducted to explain the obstacles in examining extradition cases in decision Number 369/Pid.Sus/2020/PT.DKI.JKT jo No. 04/Pid.C.Ekstradition/2020/PN.Jkt.Sel also aims to find out and describe the efforts that must be made to overcome obstacles to the implementation of extradition in the context of enforcing criminal law in Indonesia. So that the results of the study show that based on the decision there are obstacles faced by the Government of Indonesia in the application for extradition, including differences in the law and legal system, legal developments in developed and developing countries, the existence of national interests that have an impact on different perspectives of a country in fighting a crime, the extradition process is convoluted in Law No. 1 of 1979 so it will take a long time and no small amount of money, and the understanding of the implementing apparatus in extradition is minimal. Due to these obstacles, it is necessary to make efforts as an effort to overcome obstacles in examining extradition cases by looking at the extradition policies in the United States, the Philippines, and Australia which are more concise and there is a dominant role of prosecutors without involving the police or other parties and not relying on to the Minister of Foreign Affairs to receive a formal extradition request. These two things make the procedure for examining extradition cases in these countries more practical and less time-consuming. In addition, efforts that can be made are observing differences in the law and legal system, making national legal political policies concerning extradition issues, entering into extradition agreements between countries, and conducting socialization to the implementing apparatus in extradition regarding procedures and understanding of extradition laws.